2017
DOI: 10.1039/c7sc00475c
|View full text |Cite
|
Sign up to set email alerts
|

Orange, red, yellow: biosynthesis of azaphilone pigments in Monascus fungi

Abstract: Each major step leading to the classical yellow, orange and red constituents of Monascus azaphilone pigments was defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
326
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(337 citation statements)
references
References 39 publications
10
326
1
Order By: Relevance
“…Based on their UV–Visible spectra, fluorescence spectra and mass spectra, Y1 was the reported intermediate azanigerone E (Zabala et al 2012; Chen et al 2017), and we concluded that the other compounds ( Y2 – Y4 ) were novel and had not been previously reported (Table 1; Fig. 2).…”
Section: Discussionmentioning
confidence: 60%
“…Based on their UV–Visible spectra, fluorescence spectra and mass spectra, Y1 was the reported intermediate azanigerone E (Zabala et al 2012; Chen et al 2017), and we concluded that the other compounds ( Y2 – Y4 ) were novel and had not been previously reported (Table 1; Fig. 2).…”
Section: Discussionmentioning
confidence: 60%
“…Monascus species have been used for centuries in the world, especially in China, Japan, and other Asian countries, for the production of many industrially-and medically-important compounds including Monascus pigments (MPs), monacolin K and so on [1][2][3][4][5]. Each species from the genus Monascus produces unique secondary metabolites, most of which are polyketides produced by the action of a mega enzyme known as polyketide synthase (PKS) [6].…”
Section: Introductionmentioning
confidence: 99%
“…in China. It was well known that there were three kinds of pigments in monascus pigments, orange (monascorubrin – C 23 H 26 O 5 and rubropunctatin – C 21 H 22 O 5 ), red (monascorubramine – C 23 H 27 NO 4 and rubropunctamine – C 21 H 23 NO 4 ), and yellow pigment (monascin – C 21 H 26 O 5 and ankaflavin – C 23 H 30 O 5 ) . Since traditional microbial isolation and pigment extraction were replaced by novel fermentation technology and genetic engineering techniques, there are, currently, nearly 57 new pigments which are derivatives of the six well‐known pigments that already exist .…”
Section: Introductionmentioning
confidence: 99%